Implementation of Promethee II Method in the Productivity of Superior Vegetables in Sub-Districts in Northern Aceh - Meiyanti, Rini; Kautsar, Al; Fatayati, Nufus (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2025)
This research aims to determine sub-districts with superior vegetable productivity in North Aceh using the PROMETHEE II Method. This method is used in decision support systems to help analyze various criteria related to vegetable productivity, such as planting area, harvest area, added planting area, and total production. The research data was taken from 23 sub-districts in North Aceh covering various types of vegetables, such as chili, tomato, long bean, and eggplant, for the year 2023. Through analysis using the PROMETHEE Method, this research produced a ranking of sub-districts based on Net Flow values that reflected the level of productivity of each sub-district. The results show that sub-districts Tanah Luas has the highest vegetable productivity with a Net Flow value of 3.0608, while sub-districts Tanah Pasir is at the lowest position with a value of -2.2172. With these results, the research provides recommendations to the local government and farmer groups to focus on improving productivity in the low-ranked sub-districts. In conclusion, the PROMETHEE II Method provides accurate and objective results in analyzing vegetable productivity in various sub-districts and can be used as a decision-making tool related to strategies for improving vegetable agriculture in North Aceh. Therefore, the results of this study are expected to be used as guidelines in planning strategies to increase agricultural productivity in North Aceh.